KAJIAN TINGKAT PEMAHAMAN KONSEP INTEGRASI ILMU DAN ISLAM ANTARA DOSEN BIDANG ILMU UMUM DENGAN DOSEN BIDANG ILMU AGAMA DI FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SYARIF HIDAYATULLAH JAKARTA - Ansharullah Ansharullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This research is aimed to know the level of difference of Comprehension on the Concept of Integration of Science and Islam between Social - Science and Islamic Science Lecturer at Faculty of Education and Teacher Training of UIN Syarif Hidayatullah Jakarta based on the educational background, the lecturer Expertise, and the frequency of attending training on Integrating Islam and Science in Education. All lecturers were taken as sample in this research by using purposive sampling. The data was collected by using test and documentation. Then, The data was analyzed by using t-test. The results are (1) Based on the educational background of lecturer; Islamic university - graduated lecturer and Public university – graduated lecturer, the Ho hypothesis is rejected, (2) Based on the frequency of attending trainings on Integration of Science and Islam, the Ho hypothesis is accepted and, (3) based on the expertise, the Ho is rejected.